Regions/sub-regions as influences in wine selection - Shanka, Tekle; Mastaglia, Aymee (School of Marketing, Curtin Business School, 2009)
The paper discusses the extent of the influence wine regions in Western Australia (WA) have on consumers' wine purchase decisions. Participants in a structured survey were beginner to intermediate classes in the Wine Education Centre (WEC). Of the 220 completed questionnaires, 216 useable responses were analysed using SPSS v. 17. Results showed that familiar/famous wine regions and areas were most influential in wine purchase decisions for age group and self-reported wine knowledge. Results are discussed with suggestions for future research direction on individual wine producing regions.